Seguridad del neonato durante la administración de fármacos - Cabezas Niama, Anahin Nahomi (2022)
ABSTRACT: The safety of the neonate during the administration of drugs is sometimes compromised by certain factors that directly or indirectly affect it, including the characteristics of the newborn that prevent pharmacokinetics and pharmacodynamics from being carried out as an adult organism normally does. This bibliographic review was carried out through a critical reading of publications in: Scielo, PubMed, Dialnet, Redalyc, Medigraphic and Elsevier from 2017 to 2022 with the aim of describing the safety of the newborn during pharmacotherapy, answering the following questions: What adverse events occur during the administration of pharmacotherapy in neonates? What measures are taken for the safety of the neonatal patient in the administration of drugs? What are the errors that occur most frequently during the administration of drugs? According to the review of scientific literature, the adverse events that usually appear during pharmacotherapy are: toxicity due to high doses or even death due to overdose; or the opposite, that the therapeutic effect in the neonate is not achieved by very low doses. Hand washing during the 5 moments, application of the 10 correct administration and the four YO are some of the measures that are recommended to be taken to guarantee a safe infusion of medications. There are several errors that occur during pharmacotherapy, among which the following stand out: incorrect dose calculation and administration rate, use of incompatible diluents and confusion of drugs that have similar names. Through the present study it was possible to describe that during the drug administration procedure there are significant flaws that could endanger the safety of neonates. Consequently, the nursing staff must reflect on the findings to make changes in behavior and safety strategies in order to avoid errors in their management.